Pengaruh Gelatin Tulang Ikan Bandeng (Chanos chanos) terhadap Mutu Frozen Yogurt - Puspa, Elva Hariana; Abduh, Setya Budi Muhammad; Mulyani, Sri (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2023)
Frozen yogurt has the tendency to undergo recrystallization during storage, resulting in a sandy texture that necessitates the use of a stabilizer. The purpose of this study was to investigate the impact of milkfish bone gelatin on the quality of frozen yogurt, as the product may recrystallize during storage, leading to undesirable sandiness that requires a stabilizer. Various concentrations of milkfish bone gelatin stabilizer (0, 0.3, 0.6, and 0.9% (w/w)) were added to frozen yogurt, and the samples were tested for total solids, overrun, melting time, LAB profile, and sensory characteristics. The results showed that the addition of gelatin from milkfish bone increased total solids and melting time, decreased overrun, maintained the cell count of LAB, and softened the texture. However, there was no significant difference (p>0.05) observed in non-fishy aroma, white color, hedonic scores, and sour taste of frozen yogurts after one week of storage. The PCA analysis indicated distinct clusters between frozen yogurt with and without the addition of milkfish bone gelatin, which was consistent with ANOVA and Kruskal Wallis results. Based on the findings, the recommended treatment is to add 0.3% milkfish bone gelatin to frozen yogurt with a total solids content of 34.53%, overrun of 17.58%, melting time of 14.75 minutes, LAB profile of 4.2×108 CFU/mL, white color score of 7.64, non-fishy odor score of 8.40, sour taste score of 6.44, soft texture score of 7.88, and overall preference score of 8.20 (on a 1-10 scale).